Sensitivity Map Generation for Conducting Strategy In Electrical Resistance Tomography - Suzanna, Ridzuan Aw; Ruzairi, Abdul Rahim; Fazlul Rahman, Mohd Yunus; Mohd Hafiz, Fazalul Rahiman; Yasmin, Abdul Wahab; Mohd Badril, Nor Shah; Jayasuman, Pusppanathan; Elmy Johana, Mohamad (Penerbit Universiti Teknologi Malaysia, 2015)
This paper presents the sensitivity map generation of Electrical Resistance Tomography (ERT) for a system using conducting vessel pipe. A finite element model software using 2D COMSOL model consisting of 16 electrodes were attached invasively in a stainless steel pipe to solve for the forward problem. The conducting boundary approach was applied to the system to avoid the grounding effect.